Polyurethane and PTFE membranes for guided bone regeneration: Histopathological and ultrastructural evaluation - Monteiro, Adriana-Socorro-Ferreira [UNESP]; Macedo, Luis-Guilherme-Scavone [UNESP]; Macedo, Nelson-Luiz [UNESP]; Balducci, Ivan [UNESP] (Medicina Oral S L, 2010)
Objective: The purpose of this study was to research a membrane material for use in guided bone regeneration. Study design: In this study, 25 male Wistar rats were used to analyze the biocompatibility and degradation process of biomembranes. The morphological changes in subcutaneous implantations were assessed after 7, 14, 21, 28 and 70 days. The materials were made of polyurethane polymer (AUG) obtained from vegetal oil (Ricinus communis) and polytetrafluoroethylene membrane (PTFE). The surface characteristics of the physical barriers in scanning electronic microscopic (SEM) were also evaluated. Results: In both groups, the initial histological analysis showed moderate inflammatory infiltrate, which was predominantly polymorphonuclear. There was also a presence of edema, which was gradually replaced by granulation tissue, culminating in a fibrous capsule. In the AUG group, some multinucleated giant cells were present in the contact interface, with the space previously occupied by the material. However, membrane degradation was not observed during the period studied. According to the present SEM findings, porosity was not detected in the AUG or PTFE membranes. Conclusion: The researched material is biocompatible and the degradation process is extremely slow or may not even occur at all.
Keywords: Guided tissue regeneration; bone regeneration; artificial membranes; bone substitutes; polytetrafluoroethylene; polyurethane